Analysis the Influencing of Logistics Management on Decision Making for Reunion to Y Series’ Actor Fan Meeting in the Context of Thai Fan Club - Ponanake, Pareeyawadee (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The research was aimed to study 1) the influence of logistics management on decision making for reunion to Y series’ actor fan meeting in the context of Thai fan club 2) the level of the decision making for reunion to Y series’ actor fan meeting in the context of Thai fan club, and 3) the component influencing on logistics management of Y series’ actor fan meeting. The sample group was chosen using purposive sampling and consisted of 250 respondents from Thai fan club who has ever reuinoned the fan meeting of the Y series. The tool for data collection was a questionnaire. The statistics for data analysis were frequencies, percentage, and factor analysis (principle component analysis) and multiple linear regression (forward selection technique). The findings indicated that 1) two constructs of the logistics management which consists of physical flow and information & service flow have significant influencing on decision making for reunion to Y series’ actor fan meeting in the context of Thai fan club at 0.05, 2) there was high level of decision making for reunion to Y series’ actor fan meeting in the context of Thai fan club, and 3) physical flow, information & service flow can be conceptualized as component influencing on logistics management of Y series’ actor fan meeting.